2008
DOI: 10.3324/haematol.13273
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation in elderly patients (>=60 years) with diffuse large B-cell lymphoma: an analysis based on data in the European Blood and Marrow Transplantation registry

Abstract: BackgroundThere is currently limited experience on the feasibility and efficacy of autologous stem cell transplantation in elderly patients with diffuse large B-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 26 publications
7
53
2
1
Order By: Relevance
“…Accordingly to this data, there is increasing interest in performing ABSCT in older patients. In 2008, the EBMT Lymphoma Working Party showed that intensive chemotherapy followed by ABSCT is feasible in patients over 60 years and that age should not be considered as an exclusion factor [3]. This study confirmed previous data [12][13][14].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Accordingly to this data, there is increasing interest in performing ABSCT in older patients. In 2008, the EBMT Lymphoma Working Party showed that intensive chemotherapy followed by ABSCT is feasible in patients over 60 years and that age should not be considered as an exclusion factor [3]. This study confirmed previous data [12][13][14].…”
Section: Discussionsupporting
confidence: 81%
“…The upper age limit for this procedure is constantly increasing [3]. ABSCT is the standard approach for several diseases including: non-Hodgkin's lymphoma, early relapsing follicular lymphoma, mantle cell lymphoma, and patients with aggressive B and T cell lymphomas expressing bad features at the time of diagnosis (high IPI).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 2,612 patients with DLBCL receiving ASCT included 463 patients more than 60 years of age, 23% of patients being in first CR and 71% in partial remission or second or higher CR (77). When compared with younger patients, nonrelapse mortality was higher in the elderly.…”
Section: Autologous Stem Cell Transplantationmentioning
confidence: 99%
“…As such, these improvements have translated into a greater deployment of autologous HCT in patients above 60-65 years of age [8]. Contemporary registry data from the CIBMTR and the European Group for Blood and Marrow Transplantation seem to validate this practice, with seemingly no increased TRM or compromised survival outcomes in patients >65 years of age undergoing auto-HCT in patients with aggressive NHL [9], mantle cell lymphoma [10], indolent lymphomas [11] and Hodgkin lymphoma [8].…”
Section: Lymphomamentioning
confidence: 99%